Presurgical non-invasive diagnosis of focal cortical dysplasia - S. V. Mirkhaydarov (Эпилепсия и пароксизмальные состояния, 2019)
In recent decades, MRI increased the success rate of the diagnosis and surgical treatment of epilepsy. Approximately 30% of patients with epilepsy suffer from the drug-resistant form of this disease. Focal cortical dysplasia is the most common abnormality of cortical development that is often associated with drug-resistance. Surgery has an important role in the treatment of epilepsy caused by focal cortical dysplasia. Focal cortical dysplasia is classified by its morphological characteristics. By large, focal cortical dysplasia can be diagnosed using the up-to-date neuroimaging tools. The aim of that paper is to review the methods available for the diagnosis of focal cortical dysplasia.